Corporate Social Responsibility in Nepal - Shah, Krishna Kumar (Academic Voices: A Multidisciplinary Journal, 2013)
This article discusses the concept of social responsibility of corporate and its significance in Nepal. It, however, emphasizes on the part of companies/corporate to comply with and motivates their activities for the protection of vulnerable section of society for promotion of research and development activities and helps government and social institutions to face several social problems like poverty, unemployment and environmental risk and others. Academic Voices, Vol. 2, No. 1, 2012, Pages 33-37 DOI: http://dx.doi.org/10.3126/av.v2i1.8283